An Experimental Simulation to Validate FEM to Predict Transverse Young's Modulus of FRP Composites. (10th November 2013) - Sai, V. S.; Satyanarayana, M. R. S.; Murthy, V. B. K.; Rao, G. S.; Prasad, A. S.
Abstract : Finite element method finds application in the analysis of FRP composites due to its versatility in getting the solution for complex cases which are not possible by exact classical analytical approaches. The finite element result is questionable unless it is obtained from converged mesh and properly validated. In the present work specimens are prepared with metallic materials so that the arrangement of fibers is close to hexagonal packing in a matrix as similar arrangement in case of FRP is complex due to the size of fibers. Transverse Young's moduli of these specimens are determined experimentally. Equivalent FE models are designed and corresponding transverse Young's moduli are compared with the experimental results. It is observed that the FE values are in good agreement with the experimental results, thus validating FEM for predicting transverse modulus of FRP composites.